Evaluation of Usability Quality Between InDriver and Maxim Applications Using Usability Scale (SUS) and Usability Testing Methods - Janet Livia Tuwanakotta; Andeka Rocky Tanaamah (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2022)
Indriver application and Maxim application are international companies engaged in Information Technology where the company provides a platform that brings drivers and customers together quickly. Both applications come from Russia. These two applications are growing rapidly so they have been downloaded more than 5 million times through the Google Play store. Although it has been downloaded more than 5 million times, some users complain about the two applications. From some of the user feedback, the InDriver application and Maxim application still have problems that occur in their users. This problem is part of the usability problems that exist in both applications. So it is necessary to dig into a more comprehensive problem to explore the problems that occur in both applications. You also need to know the level of usability of these two applications. The level of usability needs to be known to explain the usability of these two applications is already at which level from the user side. This study provides an evaluation to determine the usability problems and the level of usability that exist in both applications using the System Usability Scale (SUS) and Usability Testing methods. The results of this study indicate that the features of the Maxim application are still not accepted by users seen from the sus questionnaire score of 48.3 and on the rating scale including the F rating with a smaller score of 51 so that it can be concluded that the Maxim application is not included in the acceptable category but not acceptable and the InDriver application has a SUS score of 51.25. On the rating scale, the InDriver application is included in the F rating so it can be concluded that the InDriver application is not included in the acceptable category but the low category.